Optimalisasi Jalur Pedestrian Antar Fakultas Di Universitas Mataram Menggunakan Algoritma Kruskal - Gilang, Gilang Primajati; M. Gunawan Supiarmo; Dita Oktavihari (Mandalika Mathematics and Educations Journal, 2025)
Efficient pedestrian pathways between faculties and key locations within the Universitas Mataram campus are a crucial aspect in supporting the academic and non-academic mobility. Optimization of pedestrian paths based on distance and connectivity efficiency between important points. This study aims to identify and optimize as well as determine the shortest pedestrian paths between faculties by applying the Kruskal algorithm, which connects all points without forming cycles based on the Minimum Spanning Tree (MST) method. There are 13 vertices representing faculties or key locations at Universitas Mataram. The distances between these faculties or places are represented as weighted edges measured in meters. A total of 15 edges were initially identified according to the algorithm’s execution. Among these, 3 edges formed cycles and had to be gradually eliminated in order to comply with Kruskal’s algorithm, resulting in the optimal solution of 12 edges for the shortest pedestrian network. The distances of these 12 edges were obtained through mapping using Google Maps. The total length of the resulting optimized pedestrian route is 2,650 meters or 2.65 kilometers. These findings can serve as a reference for policymakers at Universitas Mataram to consider in the development of network-based pedestrian infrastructure.